The Effect of Using Contextual STEAM-Based Electricity KIT in Improving Junior High School Students' Problem-Solving Ability on Dynamic Electricity Material - N. V. Utari; Fakhruddin Z; M. Nasir; R. Khairiana; R. Elinda (Journal of Science Education Research, 2023)
The study aimed to investigate the increase in problem-solving abilities of junior high school students after being treated using contextual STEAM-based electrical KIT in the experimental class and conventional learning in the control class. The research used a quasi-experimental non-equivalent control group design with the posttest-only control group design model. The population was class IX students of Muhammadiyah Middle School for the 2022/2023 academic year, with 71 students. The samples were selected using the simple random sampling technique, namely 47 students divided into class IX-1 as the control class and class IX-2 as the experimental class using a contextual STEAM-based electrical KIT. The results showed that the problem-solving ability of the experimental class was higher, namely obtaining an average score of 50.00% with sufficient criteria. Meanwhile, the control class only got an average score of 38.04% with poor criteria. Based on the inferential analysis using SPSS version 25 with a confidence level of 95%, the output of the independent t-test shows a significance of 0.009. It means that there is a significant difference between the problem-solving abilities of students who use contextual STEAM-based electrical KIT compared to students who use conventional learning.